Antifungals and acetylcholinesterase inhibitors from the stem bark of Croton heliotropiifolius - Queiroz, Marcos Marçal Ferreira [UNESP]; Queiroz, Emerson Ferreira de; Zeraik, Maria Luiza [UNESP]; Marti, G. [UNESP]; Favre-Godal, Q.; Simoes-Pires, C.; Marcourt, Laurence; Carrupt, P. A.; Cuendet, Muriel; Paulo, M. Q.; Bolzani, Vanderlan da Silva [UNESP]; Wolfender, Jean-Luc (Elsevier B.V., 2014)
The ethanolic extract of the stem bark of Croton heliotropiifolius Kunth (Euphorbiaceae) showed significant in vitro inhibition of acetylcholinesterase using a dilution spectrophotometric assay and antifungal activity against Candida albicans with a thin layer chromatography (TLC) bioautographic assay. In order to isolate the active compounds, bioassay-guided fractionation was undertaken using HPLC to localize the active compounds. Different zones of the HPLC-UV chromatogram were linked to acetylcholinesterase inhibition or to antifungal activities. In parallel to this HPLC-based activity profiling, HPLC-PDA-ESI-MS and HPLC-TOF-HRMS were used for the early identification of some of the compounds present. The targeted isolation of the active compounds was performed by medium pressure liquid chromatography (MPLC-UV) and further semi-preparative HPLC. Using this approach, nine compounds were isolated, one of them being a new indole alkaloid derivative. The structures of the isolated compounds were elucidated by spectroscopic methods including UV, NMR, MS and HRMS. (C) 2014 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.
Keywords: Croton heliotropiifolius; HPLC-PDA-ESI-MS; HPLC-TOF-HRMS; Acetylcholinesterase inhibition; Antifungal; Candida albicans